Maritime Security Policy of India in Early 21st Century: Vietnam’s Perception of Its Implication on The Asia-Pacific Region - That, Vo Van; Lam, Le Tung; Trung, Ta Quang (Universiti Utara Malaysia Press, 2023)
Since the early 21st century, the Asia-Pacific has become a dynamic region of development by some powerful countries in the world such as the United States (US), India, China, and Russia. Thus, the issue of ensuring maritime security to develop sea trade plays a central role in the strategies of these countries. From India’s perspective, maritime security in the Indian Ocean – Pacific Ocean is a deciding factor in the development, affirming its position and creating a balance of power in the country in comparison with other countries in the region. Nevertheless, the developed sea trade of India has faced challenges from various countries including the US, and China. Therefore, India has promoted a cooperative relationship with Vietnam to guarantee maritime security for Indian traders in the region. This paper aims to provide general information about maritime security as well as to determine and estimate India’s maritime security strategies. Additionally, it will present the role of Vietnam in India’s maritime security policies. The findings show that both nations, India and Vietnam have adequate backup strategies, which is the foundation for developing sea trade sustainability. Furthermore, India and Vietnam will play an increasingly strong role in the Asia-Pacific in the future.